Corpos e processos de envelhecimento: um estudo exploratório sobre a percepção de mulheres praticantes do método pilates - Motta , Luana Rossato Siqueira (2020)
The following master’s dissertation in Gerontology has as study objective to comprehend the relations between bodies and ageing in the perception of women who practice pilates method, through the conclusion that ageing process is a current subject that needs to be studied in a profound way within all its aspects. Therefore, allied with body and pilates method, this research pretended to understand how women during ageing process, in the age group from forty to seventy-three years practitioner of pilates method, sense their bodies in this moment of life, relating to the practice of pilates method, anchored to acquired knowledge from the referential material about the matter, after a qualitative approach. It was possible to conclude that women who participated in this research realize all the changes occurring with their bodies during the ageing process, sensations that comes from physical to mental issues and vary according to each age group. Through the practice of pilates method, an improvement in body perception has been observed, and they feel their bodies cared for, with better functionality and calmer to go through this phase in greater harmony with their bodies.